'Governed freedom' in Oceania: AusAID, subjectivation and the practice of critique in studies of governmentality. (December 2014) - Hodge, Paul
Abstract Drawing predominantly on the work of Butler, Rose and Walters, this paper examines the governing rationalities and technologies that characterise one particular site of aid relations. Focusing on key policy documents, economic surveys and performance reports, the paper traces the fashioning of particular subjectivities as constitutive of AusAID's development objectives and the function of problematisation and responsibilisation as central to these practices of subjectivation. While I argue the freedom on offer as part of AusAID's development objectives is a highly governed one – where the 'free' economic‐rational subject adopts certain 'civilised sensibilities' (Rose, 1999: 78), I show how this process of subjectivation encompasses both 'a power exerted on a subject' and 'a power assumed by the subject' (Butler, 1997: 11). What becomes apparent through this analysis is the productive and tenuous characteristics of these practices of subject formation. This paper also foregrounds the practice of critique itself, and the very act of research; concepts adopted and explanations made, as far from innocent in their performativity in enacting some worlds and not others.